Enhancing the ultraviolet photosensing properties of nickel oxide thin films by Zn–La co-doping. Issue 4 (15th February 2022) - Raj, I. Loyola Poul; Valanarasu, S.; Ade, Ramesh; Bitla, Yugandhar; Mohanraj, P.; Ganesh, V.; Yahia, I.S.
Abstract: In this work, co-doping effects of transition (Zn) and rare-earth (La) elements on the crystalline structure, surface morphology, photoluminescence, optical and photosensing properties of NiO thin films are studied. NiO, NiO:Zn(1%), NiO:La(1%), and NiO:Zn(1%):La(1%) thin films are fabricated using the nebulizer spray pyrolysis (NSP) method. X-ray diffraction study revealed the cubic NiO structure of all the films. Photoluminescence (PL) spectra of thin films exhibit various emission peaks centered at the wavelengths of 387, 414, 437, 451, 477, and 521 nm. The optical bandgap energy ( E g ) values are found to be 3.46, 3.43, 3.39 and 3.33 eV for NiO, NiO:Zn(1%), NiO:La(1%) and NiO:Zn(1%):La(1%) thin films, respectively. The fabricated (Zn, La) co-doped NiO i.e., NiO:Zn(1%):La(1%) photo-detector exhibits highest responsivity ( R ), external quantum efficiency (EQE) and detectivity ( D *) values of 0.50AW -1, 169% and 14.5 × 10 9 Jones, respectively as compared to NiO, NiO:Zn(1%) and NiO:La(1%) photo-detectors. The present study revealed that the transition and rare-earth elements co-doping can be an effective approach for tuning the various physical properties of semiconducting oxide films.